The Role of Modern Banking Services in Supporting the Competitive Advantage of a Sample of Private Banks in the City of Erbil, an Exploratory Study - Qader Smael, Khadeeja; Mohammed Yonis, Basm (Zanco Journal of Human Sciences, 2023)
This research deals with the knowledge of the role of modern banking services with its nine channels (independent variable) in supporting the competitive advantage with the dimensions of the five (dependent variable) for a sample of private banks in the city of Erbil, It consists of (15) banks. However, through conducting fieldwork based on the descriptive analytical method to analyze the data collected By distributing (110) questionnaires to the sample members, which were limited to those in the job (bank managers, their assistants, department officials and employees), and the ready-made statistical programs SPSS and Easy Fit were used in the analysis process. 64.6%) in the dependent variable, and this means that there is a positive (direct) relationship between the two variables. I was clear from the results that the impact of modern banking services on the dimensions of competitive advantage, but each dimension was also positive, as its greatest impact was on the flexibility dimension, as it amounted to (51.4%). The study recommended, in light of the results it reached, that banks should focus more on the dimensions of the ATM and electronic cards, as they are among the most dimensions of modern banking services that support the enhancement of competitive advantage. In addition to the higher management of banks allocating an annual financial budget for research and development, in order to Improving the quality and quality of existing banking services and innovating new ones, as well as other suggestions suggested by the study.